2017
DOI: 10.1016/j.fsi.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression analysis of chitinase genes (CHIT1, CHIT2 and CHIT3) in turbot (Scophthalmus maximus L.) following bacterial challenge

Abstract: Chitinases are hydrolytic enzymes which have been employed to breakdown chitin coats of pathogenic microorganisms, thereby weaken the defense system of several pathogens and insects. In this regard, we identified the chitinase genes of turbot and characterized their expression patterns in mucosal tissues following Vibrio anguillarum and Streptococcus iniae challenge. In present study, transcripts of three chitinase genes (CHIT1, CHIT2 and CHIT3) were captured, as well as their protein structures and expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Interestingly, during this stage, one of the most enriched GO categories was innate immune system. A significant up-regulation was detected for the chitinase family genes [ 44 , 45 ]. In addition, several genes of innate immune response were also up-regulated, including the dhx58 , ifih1 , irf3 and irf7 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, during this stage, one of the most enriched GO categories was innate immune system. A significant up-regulation was detected for the chitinase family genes [ 44 , 45 ]. In addition, several genes of innate immune response were also up-regulated, including the dhx58 , ifih1 , irf3 and irf7 genes.…”
Section: Discussionmentioning
confidence: 99%
“…The same was true for fChi3 of P. olivaceus [16], CHIT3 of Scophthalmus maximus [40], and Chi-3 of Danio rerio [41]. Furthermore, comparison of Chi-3 of S. marmoratus, Hexagrammos otakii, Sardinops melanostictus, P. olivaceus [16], and Thunnus orientalis showed homology of 45% or more probability among the five varieties of fish.…”
Section: Molecular Cloning Of Smchi-3mentioning
confidence: 74%
“…The numbers in the phylogenetic tree and [42]. Examples are chitinases in blood plasma [38] [42] and chitinases on the surface of mucous membranes, which prevent attachment to and entry of pathogens [40]. Because these chitinase genes of various fish, which were grouped into this new cluster, are widely distributed in the body, including in the liver, kidneys, brain, muscle, and blood, it was suggested that the chitinase genes belonging to this cluster are present in fish regardless of fish variety and have various physiological roles besides digestion and defense.…”
mentioning
confidence: 99%
“…Ageing leads to immunosuppression, and given the rise of drug-resistant strains of pathogens, the therapeutic options remain limited [87][88][89][90]. The role of CHIT1 in infection has been studied [21,36,[91][92][93]. Anecdotal evidence has suggested important roles for CHIT1 in host immunity, given its high concentration in anatomical sites such as the lungs and gut where there is constant exposure to microorganisms [19,94].…”
Section: Chit1 and Pulmonary Infectionsmentioning
confidence: 99%